Coded M-ary Pulse Position Modulation for Transmitted Reference UWB Communication System - Herceg, M.; Milanovic, J.; Vranjes, M. (Elektronika ir Elektrotechnika, 2014)
In this paper, a coded M-ary pulse position modulation (PPM) scheme for transmitted reference ultra-wideband (TR-UWB) systems is proposed. In conventional M-ary PPM TR-UWB scheme, modulation level M is defined only with a number of possible pulse positions Z. So, Z radio frequency (RF) wideband delay lines are required in order to map data bits into the proper pulse position, which makes such system very impractical to implement when the current CMOS technology is used. In the proposed scheme the number of required delay lines is reduced by mapping data bits in both, pulse position and K different orthogonal codes on frame level of the signal, producing a modulation level of M = KZ. To evaluate the performances of the proposed coded M-ary PPM scheme, the analytical model for realistic IEEE standard UWB channel models is developed. The performances of the proposed scheme are compared with these of the conventional M-ary PPM scheme for the same modulation level M. The results show that the proposed coded M-ary PPM scheme achieves approximately the same bit error probability (BEP), higher data rate and higher bandwidth efficiency, while the hardware complexity is lower in terms of number of required RF delay lines. However, by increasing the number of used orthogonal codes the minimum number of frames per one information symbol rises and consequently the maximum achievable data rate is limited. Thus the trade-off between the number of orthogonal codes and target data rate should be made. DOI: http://dx.doi.org/10.5755/j01.eee.20.10.6797